POTENSI BAHAYA TANAH LONGSOR DI SUB DAS LEMATANG KOTA PAGAR ALAM - Dwi Putri Juliana; Alharia Dinata; Barrorotul Azizah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
: Landslides are mass transfer processes. Landslides are occured because there are differences in the equilibrium of forces acting on the slope, namely the restraining force and launch force. The method used in analyzing the potential for landslides in the Lematang watershed of Pagar Alam was the GIS (Geographic Information System) method. Within the parameters was given weight and score respectively in the class of Slopes, Land Use, Soil Type, Topography. Based on the results of the overlay to the four parameters, obtained based on the analysis of the potential distribution of landslide-prone blood by 19%, Low 20%, Medium 11%, High 27%, Very High 23%.